Implementation of the market approach to the processes of management of the energy sector of ukrainian economy under conditions of European integration - Dergachova, Victoria; Pysar, Nadiia (Eastern-European Journal of Enterprise Technologies, 2018)
We developed the system of differential equations, which describes the level of supply of energy products (production and import) and demand for them (consumption). The equations take into consideration factors of prices for fuel-and-energy resources, exports, imports, as well as a mutual influence of the volumes of production of certain types of energy resources on others. We performed calculation of production, consumption and consumption of fuel-and-energy resources based on the constructed system. We obtained a normal system of linear differential equations of the first order, which describes the dependence between 7 resource components of the fuel-and-energy complex (gas, oil, black oil, coal, uranium, electricity, and thermal energy). Efficient functioning of the energy market requires validity and transparency in the management of processes occurring in its system in the form of interaction of subsystems. The proposed holistic system of differential equations makes it possible to assess an energy supply potential of the energy market in accordance with the needs of consumers based on data on the level of reserves at the beginning of a year and production and consumption over the past year. Given such a model, it is possible to forecast daily levels of consumption and supply of energy resources, taking into consideration seasonality of thermal energy production. Despite many equations and dependent variables, we found a numerical solution to the system. We used calculation formulas from the Euler method with step h=1 for this purpose. We obtained the solution in the form of tabulated values of functions of production or consumption of the corresponding energy resources. Based on the results of calculations, we built a graph of the corresponding dependences of parameters of the system of differential equations. We used the system of computer algebra wxMaxima for calculations. Economic-mathematical modeling of energy market management processes is useful because it makes it possible to describe the resulting state of the energy market in Ukraine parametrically and opens up additional possibilities of forecasting taking into consideration stochastic phenomena of price and temperature.